2016
DOI: 10.1111/jai.13022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed discharges from a hydropower station on summer diel feeding activity and diet of brown trout (Salmo trutta Linnaeus, 1758) in an Iberian stream

Abstract: SummaryThe influence of pulsed discharges associated with hydroelectric power generation (i.e. hydropeaking) on feeding activity and diet composition of adult brown trout (Salmo trutta) was studied during summer by comparing two sites: upstream (control site) and downstream from a power plant (hydropeaking site). Twenty fish were captured from each study site by electrofishing at four-hour intervals for two consecutive days and stomach contents were collected with pulsed gastric lavage. Hydropeaking events aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…There were no significant differences in trout diel activity, thus suggesting that brown trout individuals were active during the day and night. These results agree with a recent study showing an absence of diel cycling in the summer feeding activity of brown trout in the study area (Rocaspana et al, ), and other works reporting that brown trout individuals are active during the day and night in summer (Clapp et al, ; Young, Wilkison, Phelps, & Griffith, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…There were no significant differences in trout diel activity, thus suggesting that brown trout individuals were active during the day and night. These results agree with a recent study showing an absence of diel cycling in the summer feeding activity of brown trout in the study area (Rocaspana et al, ), and other works reporting that brown trout individuals are active during the day and night in summer (Clapp et al, ; Young, Wilkison, Phelps, & Griffith, ).…”
Section: Discussionsupporting
confidence: 94%
“…Because flow fluctuations caused by hydropeaking exceed those observed naturally (Poff et al, ), negative impacts on riverine organisms such as benthic invertebrates and fish are expected. For example, the resulting rapid changes in river discharge affect the invertebrate drift (Bruno, Siviglia, Carolli, & Maiolini, ; Gibbins, Vericat, & Battala, ; Lauters, Lavandier, Lim, Sabaton, & Belaud, ; Rocaspana, Aparicio, Vinyoles, & Palau, ) and reduce both the quantity and quality of habitat available to fish (Liebig, Cereghino, Lim, Belaud, & Lek, ; Person, ; Young, Cech, & Thompson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dedual & Collier, ). Studies with brown trout ( Salmo trutta ) have shown higher food consumption rates during hydropeaking flow pulses as an opportunistic response to increased prey availability (Rocaspana, Aparicio, Vinyoles, & Palau, ), effectively coupling the two opposing impacts of increased food supply, and increased energy expenditure driven by hydropeaking. However, regulation‐derived increases in activity (metabolic demands) may not always be offset by increases in food supply, making generalisations about dam impacts difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid fluctuations in water flow can also affect temporal aspects of stream fishes behaviour, for example, small and large‐scale movements, relocation, and habitat use (Korman & Campana, ; Krimmer, Paul, Hontela, & Rasmussen, ; Riley, Maxwell, Pawson, & Ives, ; Scruton et al, ; Taylor et al, ). Other studies have suggested that salmonids also alter their diel feeding activity in response to hydropeaking (e.g., Rocaspana, Aparicio, Vinyoles, & Palau, ). Salmonids show extensive flexibility in diel activity (Reebs, ) and can adjust it in response to daily variations of food availability and predation risk (Larranaga & Steingrímsson, ; Orpwood, Griffiths, & Armstrong, ).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid fluctuations in water flow can also affect temporal aspects of stream fishes behaviour, for example, small and large-scale movements, relocation, and habitat use (Korman & Campana, 2009;Krimmer, Paul, Hontela, & Rasmussen, 2011;Riley, Maxwell, Pawson, & Ives, 2009;Scruton et al, 2005;Taylor et al, 2014). Other studies have suggested that salmonids also alter their diel feeding activity in response to hydropeaking (e.g., Rocaspana, Aparicio, Vinyoles, & Palau, 2016).…”
mentioning
confidence: 99%